Effect of Mixing Wheat Flour with Pumpkin and Dates on the Nutritional and Sensory Characteristics of Cake - Aljahani, Amani Hamzah; Al-Khuarieef, Amal Nassir (Pakistan Journal of Nutrition, 2017)
Background: The development of food products is a major goal of the food industry. Pumpkin is a rich source of nutrients that may help improve products. Objective: The aim of this study was to evaluate the effect of replacing wheat flour with pumpkin or both pumpkin and dates on the chemical and sensory characteristics of cake. Methodology: Three different cakes were prepared: (1) Control, (2) 50% of the wheat flour replaced with pumpkin mash and (3) 50% of the wheat flour replaced with 30% pumpkin and 20% dates. The moisture, protein, fat, ash, fiber, carbohydrate and fatty acid contents were measured. Results: There were no significant differences (p